2012
DOI: 10.1002/prot.24132
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced fibrils formation of chicken egg white lysozyme under native conditions

Abstract: Recent findings showed that transiently accessing structurally native-like yet energetically higher conformational states is sufficient to trigger the formation of protein fibrils. Typically, these conformational states are made available through changing solvent conditions or introducing mutations. Here we show a novel way to initialize fibril formation for Chicken egg white lysozyme (CEWL) under native conditions via controlled UV illumination. Through a cassette of tryptophan-based photochemistry, the two t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 67 publications
(108 reference statements)
2
20
0
Order By: Relevance
“…Remarkably, our simulations capture the extent of rate changes found in experiments quantitatively, thus establishing the crucial role the β-hairpin plays in enabling to form. More recently, experiments have further illustrated the link between hydrophobic interactions and disulfide bond formation in controlling fibrillar and globular aggregate formation in egg white lysozyme (30,31).…”
Section: Stability Of β-Hairpinmentioning
confidence: 99%
“…Remarkably, our simulations capture the extent of rate changes found in experiments quantitatively, thus establishing the crucial role the β-hairpin plays in enabling to form. More recently, experiments have further illustrated the link between hydrophobic interactions and disulfide bond formation in controlling fibrillar and globular aggregate formation in egg white lysozyme (30,31).…”
Section: Stability Of β-Hairpinmentioning
confidence: 99%
“…3 [25]. The two disulfide bonds Cys6-Cys127 and Cys30-Cys115 which connect the two termini of CEWL can be selectively reduced through tryptophan-mediated photo-reduction process.…”
Section: Self-assembly Mechanism Of Cewl Fibrillar Aggregatesmentioning
confidence: 99%
“…We found that the unfolding and self-assembly of UV-illuminated proteins can be well controlled by adjusting the illumination time and intensity of UV light. Under different illumination conditions, the diversity of self-assembled nanoparticles can be easily realized from several nanometers to several micrometers, and even the formation of amyloid-like fibrils [23][24][25]. In fact, the sizes of these globular nanoparticles are quite dependent with the exposure of hydrophobic amino acids of illuminated proteins and their stability is dominated by the newly formed intermolecular disulfide bond.…”
Section: Introductionmentioning
confidence: 98%
“…Because of its easy incorporation into peptides and proteins, early attempts have explored the utility of using a disulfide as a phototrigger [53]. While these studies showed that disulfides can be cleaved with ultraviolet light (∼270 nm) [54, 55], the free radicals formed upon photoexcitation often undergo ultrafast geminate recombination and are also very reactive, making it a less-than-ideal trigger. Recently, several studies have shown that it is possible to remediate these pitfalls.…”
Section: Triggering Protein Conformational Events With Lightmentioning
confidence: 99%